Understanding the morphology evolution of 1D BiVO4 nanoarrays from nanorods to nanocones with enhanced photocatalytic performance. Issue 17 (7th April 2022) - Yang, Nengcong; Bao, Yunfeng; Guo, Xiangyang; Lian, Juhong; Wu, Chao; Qi, Yu; Zhang, Fuxiang
Abstract : The controllable synthesis of BiVO4 nanocone and nanorod arrays is reported. The morphology transformation of BiVO4 nanoarrays is accompanied with growth mechanism transformation and the tip structure results in superior photocatalytic performance. Abstract : Photocatalysts with tailored nanoarchitectures allow the regulation of their physical and chemical properties via dimensional growth and crystal facet engineering, etc. Fabricating one-dimensional (1D) nanostructures, such as nanowires, nanorods, and nanotubes, have proved to be an effective strategy for promoting charge separation and performance in photocatalysis. However, the controllable synthesis of 1D semiconductor photocatalysts is still a great challenge due to the limited understanding of the growth mechanism, especially for the different 1D structural morphologies. Herein, 1D BiVO4 nanoarrays, with regular square-shaped nanorod and tapered nanocone morphologies, were synthesized via a precise control of the growth parameters in aqueous solution. Also, the morphology evolution from the square-shape nanorods to tip-tapered nanocones during the formation of the 1D BiVO4 nanostructure arrays was studied by systematic investigations. This phenomenon was further investigated by dividing the growth process into two characteristic stages dominated by the crystallization growth to the particle attachment assembly. Benefiting from the controllable nanostructure, we found that the tips of the nanocone structure facilitated charge separation, leading to enhanced performance in the photocatalytic reaction of methylene blue (MB) degradation. This study enriches our understanding of the general behavior of nanostructured crystal growth and provides a facile strategy to achieve the rational morphology design of efficient semiconductor photocatalysts.